STRATEGI ALIH FUNGSI LAHAN TAMBAK MENJADI SAWAH DENGAN PENDEKATAN BIOEOLOGI DI KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG - Muh Reza Fikriawan; Muhammad Kasnir; Hasnidar Hasnidar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
The conversion of fish ponds into rice fields in Mattiro Sompe Subdistrict, Pinrang Regency, is a response to declining pond productivity due to environmental degradation and socio-economic shifts. This study adopts a bioecological approach and SWOT analysis to formulate sustainable land management strategies. Findings indicate that internal strengths include clay–loam soil texture, low salinity, and strong farmer interest, while key weaknesses involve distance from irrigation sources and acidic soil conditions. Externally, opportunities arise from government subsidy programs and adaptive rice varieties, whereas significant threats include climate change and seawater intrusion. With an IFAS score of +0.47 and EFAS score of –0.60, the strategy falls into Quadrant II (Strength–Threat), highlighting the need for adaptive policies that leverage internal strengths to mitigate external risks and achieve sustainable land-use transitions.